2007
DOI: 10.1128/mcb.01122-06
|View full text |Cite|
|
Sign up to set email alerts
|

Hepatic De Novo Lipogenesis Is Present in Liver-Specific ACC1-Deficient Mice

Abstract: Acetyl coenzyme A (acetyl-CoA) carboxylase (ACC) catalyzes carboxylation of acetyl-CoA to form malonylCoA. In mammals, two isozymes exist with distinct physiological roles: cytosolic ACC1 participates in de novo lipogenesis (DNL), and mitochondrial ACC2 is involved in negative regulation of mitochondrial ␤-oxidation. Since systemic ACC1 null mice were embryonic lethal, to clarify the physiological role of ACC1 in hepatic DNL, we generated the liver-specific ACC1 null mouse by crossbreeding of an Acc1 lox(ex46)… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

5
41
0

Year Published

2007
2007
2023
2023

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 104 publications
(46 citation statements)
references
References 32 publications
5
41
0
Order By: Relevance
“…To further elucidate the role of ACC1 in liver de novo lipogenesis, two liver-specific ACC1-knockout mouse models have been generated using Cre- lox/P system (63; 64). Mao et al reported that on standard chow diet ACC1 knockout mice accumulate less triglycerides in their livers and have decreased malonyl-CoA levels.…”
Section: Enzymes Of De Novo Lipogenesis and Nafldmentioning
confidence: 99%
See 1 more Smart Citation
“…To further elucidate the role of ACC1 in liver de novo lipogenesis, two liver-specific ACC1-knockout mouse models have been generated using Cre- lox/P system (63; 64). Mao et al reported that on standard chow diet ACC1 knockout mice accumulate less triglycerides in their livers and have decreased malonyl-CoA levels.…”
Section: Enzymes Of De Novo Lipogenesis and Nafldmentioning
confidence: 99%
“…When fed a fat-free diet for 10 days, mice with liver specific ACC1 knockout had significant up-regulation of several enzymes in the fatty acid synthesis pathway, again indicating that dietary carbohydrates may compensate for a loss of single DNL enzyme (63). Surprisingly, in a study by Harada at al., liver specific ACC1 knockout did not alter hepatic DNL or malonyl-CoA levels, however, hepatic DNL was completely inhibited by the dual ACC1 and ACC2 inhibitor, 5-tetradecyloxyl-2-furancarboxylic acid (64). In both of these models compensatory upregulation in ACC2 expression was observed, making the interpretation of ACC1 knockout in these studies challenging.…”
Section: Enzymes Of De Novo Lipogenesis and Nafldmentioning
confidence: 99%
“…2 Recent studies reported by Harada et al indicate that hepatic ACC2 could partially cover ACC1 function as a backup system. 3 Consequently, reduction of malonyl-CoA levels in these tissues by ACC1/2 non-selective inhibitors is expected to reduce de novo fatty acid synthesis and triglyceride (TG)-rich lipoprotein secretions in liver while increasing fatty acid b-oxidation in liver and skeletal muscle. Therefore, an ACC1/2 non-selective inhibitor might provide a novel therapeutic approach for treating various metabolic disorders.…”
Section: Introductionmentioning
confidence: 99%
“…Liver lipids were extracted and analyzed as described previously (6). De novo lipogenesis in mouse primary hepatocytes was analyzed using sodium [2-14 C]acetate (PerkinElmer Life Sciences) as described previously (65). Lipogenic activity was presented as normalized radioactivity (counts per min (cpm)) to protein amount.…”
Section: Methodsmentioning
confidence: 99%